Effector innovation in genome-reduced phytoplasmas and other host-dependent mollicutes - Mirkin, Federico G.; Mugford, Sam T.; Thole, Vera; Marzo, Mar; Hogenhout, Saskia A. (PLOS Genetics, 2025)
Author Summary Phytoplasmas are minute bacteria that inhabit plants and their sap-feeding insect vectors. Infected plants often show striking developmental abnormalities, such as excessive shoot proliferation and the conversion of flowers into leaf-like structures (phyllody). These changes frequently lead to sterility, redirecting the plant resources in ways that facilitate bacterial transmission. Because phytoplasmas depend on their hosts and rarely get an opportunity to pick up new virulence genes from other bacteria, their virulence factors likely diversify through other means, evolving features that let them fine-tune plant and insect-vector processes, including dampening their immune responses. To explore how such diversity has arisen, we analysed 239 phytoplasma genomes and identified a large repertoire of candidate virulence factors, which we term Phytoplasma Effectors (PhAMEs), encompassing established factors and many previously unrecognised ones. By predicting and studying their structures, we uncovered strategies of molecular innovation and gained insight into how these effectors interact with host proteins. Comparative analyses against proteins from other pathogenic bacteria, including those that infect humans, revealed both conserved and lineage-specific strategies of host manipulation. Our findings show how even the most genome-reduced bacteria can evolve sophisticated tools to manipulate their multicellular hosts, offering new perspectives for biology and biotechnology.